Performance Audit of Employees State Insurance Corporation (ESIC 1999-2004) - CAG of India (CAG of India, 2006)
This Report contains the result of Performance audit of Employees’ State Insurance Corporation (ESIC) for the period 1999-2000 to 2003-04. This performance audit was conducted to assess: (i) whether the ESIC has achieved its objective of providing the full range of medical care; (ii) adequacy of ESIC's financial management; (iii) extent to which eligible establishments and were covered in ESIS, (iv) economy, efficiency and effectiveness of ESIC's construction and procurement activities; and (v) extent to which the model hospitals met their objectives.
For the Period 1999-2000 to 2003-04